SEROPREVALENCIA DEL VIRUS DE LA DIARREA VIRALBOVINA EN GANADO LECHERO DE CRIANZA INTENSIVA DEL VALLE DE LIMA - Aguilar S., Renzo (2012)
The prevalence of bovine viral diarrhea virus (BVDV) was determined in 12 dairy herds of the Lima valley. Blood samples were taken in 311 female cattle older than 6 months of age for the detection of antibodies against BVDV by viral neutralization test. The herds did not have history of vaccination against bovine viral diarrhea disease. The prevalence of BVDVwas 56.0 ± 5.5%(174/311) and the titers of antibodies againstBVDV ranged from 2 to >256. Five out of the 12 herds did not have seropositive animals. The results indicated that the BVDV was widely distributed in dairy herds of Lima valley; although viral prevalence is low and some herds are free of the disease.